Geologic and geotechnic analysis of the Mandaguari municipality cemetery, State of Paraná - Martim, Aline Giseli; Angelis, Bruno Luiz Domingos de; Angelis Neto, Generoso de; Silva, Frederico Fonseca da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Based on the assumption that the horizontal burial of bodies and their subsequent decomposition into cemeteries can potentially cause contamination of groundwater, this work aims at the construction of a geological report for the horizontal municipal cemetery of Mandaguari (Brazil), analyzing all geological characteristics of the region where was installed this venture. Thus, the preparation of this report, was focus on the enforcement of the Resolutions 019/04 and 016/05 of the Secretary of State for the Environment and Water Resources - SEMA and the Resolution 357/05 of the National Council on the Environment - CONAMA, at the request of the Office for the Environment of Parana - IAP.